2009
DOI: 10.4161/cbt.8.18.9207
|View full text |Cite
|
Sign up to set email alerts
|

A role for p53 in the regulation of extracellular matrix metalloproteinase inducer in human cancer cells

Abstract: EMMPRIN, a transmembrane glycoprotein known to promote survival, invasion and metastasis of tumor cells through multiple pathways and mechanisms, has been found to be overexpressed in various types of cancer cells. Here we report that loss of the function of p53, a tumor suppressor protein that is mutated in approximately 50% of human cancers, contributes to the upregulation of EMMPRIN protein. We observed an inverse association between the activity of p53 and the level of EMMPRIN protein in several cancer cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 35 publications
1
10
0
Order By: Relevance
“…In addition, ATA failed to inhibit migration and invasion of HBCCs under p53 knock-down. Our results were consistent with previous reports that induction of p53 downregulates MMPs activity and inhibits tumor cell invasion [42].…”
Section: Discussionsupporting
confidence: 94%
“…In addition, ATA failed to inhibit migration and invasion of HBCCs under p53 knock-down. Our results were consistent with previous reports that induction of p53 downregulates MMPs activity and inhibits tumor cell invasion [42].…”
Section: Discussionsupporting
confidence: 94%
“…In the classical p53-dependent pathway G 2 /M phase arrest, activation of p53 interacts with response elements present on the promoter region of p21 to increase expression of p21, which subsequently interacts with CDKs and cyclins to affect cell cycle arrest [23]. Here in the present studies, the expressions of p21 were increased by α-santalol treatment in both cell lines; the expressions of mutated p53, that is overexpressed in most of cancer cells [36], were decreased after α-santalol treatment in A431 cells and expressions of wild-type p53 were increased by α-santalol in UACC-62 cells, all of which may contribute to α-santalol's overall chemopreventive effects against skin cancer. However, knockdown of either p21 or wild-type p53 did not change G 2 /M phase arrest caused by α-santalol, which suggested that α-santalol induced G 2 /M phase arrest independently of p21 and p53.…”
Section: Discussionmentioning
confidence: 69%
“…Previous studies have shown that EMMPRIN/CD147, through multiple pathways and mechanisms, stimulates adjacent fibroblasts to produce matrix metalloproteinases, and thus promotes survival, invasion and metastasis of tumor cells (13,(18)(19)(20)(21)(22)(23)36). Indeed, EMMPRIN/CD147 expression is correlated significantly with the stage of clinicopathology in thyroid carcinoma (9), adenocarcinomas (7), esophageal squamous cell carcinomas (37) and prostate cancer (14).…”
Section: Discussionmentioning
confidence: 92%
“…EMMPRIN/CD147 promotes survival, invasion and metastasis of tumor cells through multiple pathways and mechanisms, including the functional loss of p53, a tumor suppressor (18), upregulated expression of vascular endothelial growth factor (VEGF) (13,(19)(20)(21), disruption of transforming growth factor-β1 (TGF-β1), a growth-modulating factor (22), and regulation of the urokinase-type plasminogen activation (uPA) system of serine proteases (23). Therefore, EMMPRIN/CD147 has been suggested potentially as a prognostic biomarker for certain types of tumors and as a therapeutic target (24).…”
Section: Introductionmentioning
confidence: 99%